Atividade virucida de um extrato etanólico de própolis verde in vitro e in vivo - Nunes, Cristina Freitas (2011)
Currently, the drug industry looks for new drugs based on natural products, for the production of drugs more efficient, for which the microorganisms did not show resistance to both humans and animals. A natural product that has been the subject of intense pharmacological and chemical studies by scientists for the control of diseases is propolis, a resinous substance produced by honeybees from exudates collected from different parts of the plant, which has been used for centuries in popular medicine due to its therapeutic properties. Chemical studies revealed the complex chemical composition, identifying in some cases more than 300 components including various bioactive phenolic compounds responsible for the virucidal action. This work initially describes the standardization of an ethanol extract of green propolis (EEPV), where the chemicals were identified by high performance liquid chromatography (HPLC), phytochemical characterization by thin layer chromatography (TLC), soluble solids, content of phenolics and flavonoids and antioxidant activity by 2.2 diphenil picryl hydrazyl (DPPH). The EEPV was also evaluated in vitro and in vivo for their capacity lentogenic virucidal against a strain of the virus of Newcastle disease (NDV) at two different temperatures (22 and 37 ° C), 5 incubation periods (0, 1, 2, 4 and 8 hours) of NDV in five different concentrations of EEPV (4000μg/dose, 400μg/dose, 40μg/dose, and 4μg/dose 0μg/dose). The EEPV standard is within the standards required by the MAP, with high levels of phenolics and flavonoids (12.93 and 6.05% respectively) as shown by HPLC, which identified high concentrations of phenolic acids (p-coumaric acid, hydroxycinnamic acid diprenyl , cinâmino acid derivatives), which are assigned the antibacterial, antioxidant, antiviral and virucidal. This extract showed dose-dependent virucidal activity (4000μg/dose e 400μg/dose) and time of incubation with the virus (2 hour). The inhibitory activity of EEPV against the strain of NDV lentogenic found in the present study suggests the use of this extract as an alternative to fight the infection by this virus.